2018
DOI: 10.1021/acs.analchem.7b03784
|View full text |Cite
|
Sign up to set email alerts
|

Correction for the Hematocrit Bias in Dried Blood Spot Analysis Using a Nondestructive, Single-Wavelength Reflectance-Based Hematocrit Prediction Method

Abstract: The hematocrit (Hct) effect is one of the most important hurdles currently preventing more widespread implementation of quantitative dried blood spot (DBS) analysis in a routine context. Indeed, the Hct may affect both the accuracy of DBS methods as well as the interpretation of DBS-based results. We previously developed a method to determine the Hct of a DBS based on its hemoglobin content using noncontact diffuse reflectance spectroscopy. Despite the ease with which the analysis can be performed (i.e., mere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…More straightforwardly, strategies for the assessment of HCT post‐sampling from DBS can be established in a centralized laboratory. Thereby, the HCT assessment is either destructive (requiring the extraction of a DBS) 45,46 or non‐destructive (measuring the DBS's surface) 47–51 . As each collected sample is precious, the main focus of the HCT strategy should be on non‐destructive HCT determination.…”
Section: Measurement Of Hct In Dbsmentioning
confidence: 99%
See 4 more Smart Citations
“…More straightforwardly, strategies for the assessment of HCT post‐sampling from DBS can be established in a centralized laboratory. Thereby, the HCT assessment is either destructive (requiring the extraction of a DBS) 45,46 or non‐destructive (measuring the DBS's surface) 47–51 . As each collected sample is precious, the main focus of the HCT strategy should be on non‐destructive HCT determination.…”
Section: Measurement Of Hct In Dbsmentioning
confidence: 99%
“…However, they concluded that differences in temperature or humidity might influence the molecular vibrations of the DBS matrix, thus negatively influencing the outcome of the used DBS NIR spectrometry measurement. The use of reflectance‐based DBS HCT measurement does not have this limitation 48,49 . An application of fully automated DBS analysis with reflectance‐based HCT correction has been realized (unpublished).…”
Section: Measurement Of Hct In Dbsmentioning
confidence: 99%
See 3 more Smart Citations